How to cheat at designing security for a Windows Server 2003 network - Amini, Rob.; Hunter, Laura E. (Rockland, Mass. : Syngress Pub., 2006)
Annotation Windows 2003 Server is unquestionably the dominant enterprise level operating system in the industry, with 95% of all companies running it. And for the last tow years, over 50% of all product upgrades have been security related. Securing Windows Server, according to bill gates, is the company's #1 priority. While considering the security needs of your organiztion, you need to balance the human and the technical in order to create the best security design for your organization. Securing a Windows Server 2003 enterprise network is hardly a small undertaking, but it becomes quite manageable if you approach it in an organized and systematic way. This includes configuring software, services, and protocols to meet an organization's security needs. * The Perfect Guide if "System Administrator is NOT your primary job function * Avoid "time drains" configuring the many different security standards built into Windows 2003 * Secure VPN and Extranet Communications.
Designing a secure network framework -- Securing servers based on function -- Designing a secure public key infrastructure -- Securing the network management process -- Securing network services and protocols -- Securing internet information services -- Securing VPN and extranet communications -- Securing active directory -- Securing network resources -- Securing network clients.
Title from title screen.
Includes index.
Keywords: Computer networks -- Security measures; Database security; Computer security; Microsoft Windows server; Electronic books